An experimental study on the mechanisms of enhancing oil recovery by nanoparticles-assisted surfactant flood. Issue 6 (1st November 2020) - Mobaraki, Sina; Zakavi, Mahdi; Mahmoodi, Omid; Omidvar Sorkhabadi, Milad; Khalilinezhad, Seyyed Shahram; Shiri Torkmani, Reza
ABSTRACT: The central concern of this study is to examine the synergic effects of an anionic surfactant and hydrophilic silica nanoparticles on the improvement of surfactant properties. The assessment of the effect of silica nanoparticles on the emulsification ability of the surfactant solution was performed by the use of both electrical conductivity measurements and phase behavior tests. Accordingly, an optimal chemical formulation for the utilized crude oil was suggested. Optical absorption technique was also employed to evaluate the stability of the optimal solution. The oil recovery experiments were carried out in a transparent glass micromodel saturated with crude oil to monitor some pore-scale displacement events during the simultaneous flow of the optimal solution and the crude oil through porous media. Phase behavior tests indicated that the silica nanoparticles are effective in terms of Interfacial tension (IFT) reduction since they can achieve ultra-low IFT level. The results of conductivity experiments proved the ability of silica nanoparticles to reduce the Critical Micelle Concentration (CMC) of the surfactant. The stability tests proved that the optimal solution is stable for a reasonable time. The multiphase flow experiments revealed that oil recovery increased by about 5% during nanoparticles-assisted surfactant flooding compared with surfactant flood.